Same but not The Same: Describing and Shaping Meaning-making in Engineering Mathematics Problems - de Andrade, Matheus; Dahl, Bettina; Wolff, Karin (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Existing paradigms for mathematics education emphasise self-regulated learning, modelling competencies, and learning outcomes in all cognitive, psychomotor and affective domains of learning. However, there is a gap in the engineering education literature with regards to meaning making of mathematics concepts as applied to engineering problems. This paper is written as a configurative dialogue between two educators delivering and supporting teaching and learning of mathematics in two different European contexts and one supporting learning in a South African context. In sharing our practices, we realised that although an exhaustive list of frameworks for mathematics education exists, telling them apart in the context of engineering mathematics education can be difficult and often adds little actionable insights. This realisation motivates the title of this paper “Same but not The Same”. We use the semantic plane of Legitimation Code Theory (LCT) to reflect on problem or scenario-based learning of abstract and/or complex mathematics topics such as linear algebra and differential equations through examples of their (engineering) applications. We argue that qualitative descriptions of meaning-making in open-ended, real-life mathematics problems, methods, and tasks are scarce, and that this can create significant challenges for educators to describe, share, and shape their practices.